2006
DOI: 10.1099/ijs.0.64255-0
|View full text |Cite
|
Sign up to set email alerts
|

Sulfurimonas paralvinellae sp. nov., a novel mesophilic, hydrogen- and sulfur-oxidizing chemolithoautotroph within the Epsilonproteobacteria isolated from a deep-sea hydrothermal vent polychaete nest, reclassification of Thiomicrospira denitrificans as Sulfurimonas denitrificans comb. nov. and emended description of the genus Sulfurimonas

Abstract: Sulfurimonas paralvinellae sp. nov., a novel mesophilic, hydrogen-and sulfur-oxidizing chemolithoautotroph within the Epsilonproteobacteria isolated from a deep-sea hydrothermal vent polychaete nest, reclassification of Thiomicrospira denitrificans as Sulfurimonas denitrificans comb. nov. and emended description of the genus Sulfurimonas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
202
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(212 citation statements)
references
References 42 publications
7
202
1
2
Order By: Relevance
“…In addition, anaerobic denitrification is suggested to be a common process in the studied lakes as indicated by the presence of Sulfurimonas and the oversaturation of N 2 in the suboxic hypolimnia . Sulfurimonas isolates represent sulphur-oxidizing chemolithoautotrophs (for example, Inagaki et al, 2003;Takai et al, 2006) that can perform autotrophic denitrification. This chemolithotrophic process couples denitrification with the oxidation of reduced inorganic sulphur compounds and members of the genus Sulfurimonas have been identified as the main denitrifiers in chemoclines of the Baltic Sea (Glaubitz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, anaerobic denitrification is suggested to be a common process in the studied lakes as indicated by the presence of Sulfurimonas and the oversaturation of N 2 in the suboxic hypolimnia . Sulfurimonas isolates represent sulphur-oxidizing chemolithoautotrophs (for example, Inagaki et al, 2003;Takai et al, 2006) that can perform autotrophic denitrification. This chemolithotrophic process couples denitrification with the oxidation of reduced inorganic sulphur compounds and members of the genus Sulfurimonas have been identified as the main denitrifiers in chemoclines of the Baltic Sea (Glaubitz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The nirK clones in Clusters I-IV and the nirS clones in Clusters I and II were obtained from all environmental samples examined, that is, cropland, rice paddy, forest soils and lake sediment (Figures 2 and 3) (Supplementary Table S3). The nirS clones in Cluster III, which contained the entire nirS sequence from deep-sea sediments in hydrothermal fields (Takai et al, 2006), were not obtained from these environmental samples.…”
Section: Diversity Of Nirk and Nirs Genes In Various Environmentsmentioning
confidence: 99%
“…However, the isolation and characterization of a number of novel bacteria and archaea from deep-sea hydrothermal vents revealed that most of them can use nitrate in addition to sulfur as their terminal electron acceptor. During growth, these microorganisms reduce nitrate to dinitrogen (Takai et al, 2004;Nakagawa et al, 2005;Takai et al, 2006) or ammonium (Blochl et al, 1997;Vetriani et al, 2004;Voordeckers et al, 2008;Perez-Rodriguez et al, 2010, 2012. In most cases, nitrate reduction is coupled to the oxidation of molecular hydrogen (and less frequently of formate or thiosulfate), and these organisms have a shorter doubling time when nitrate, rather than sulfur, is supplemented as the terminal electron acceptor (Vetriani et al, 2004;Voordeckers et al, 2005;Perez-Rodriguez et al, 2010, 2012.…”
Section: Introductionmentioning
confidence: 99%